Results 1 to 9 of 9

Math Help - How can you prove this?

  1. #1
    Junior Member
    Joined
    Jan 2009
    Posts
    44

    How can you prove this?

    \sum_{n=1}^{{\color{red}\infty}}r^n

    I'm assuming this is the correct way to write;

    r+r^2+r^3+r^4 . . . r^n where the n goes on for infinity.


    So how can you prove;

    \sum_{n=1}^{{\color{red}\infty}}r^n = \frac{r}{1-r}
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Math Engineering Student
    Krizalid's Avatar
    Joined
    Mar 2007
    From
    Santiago, Chile
    Posts
    3,654
    Thanks
    13
    Hint: r^{n}=\frac{r^{n}-r^{n+1}}{1-r}, and use telescoping series.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Junior Member
    Joined
    Jan 2009
    Posts
    44
    Quote Originally Posted by Krizalid View Post
    Hint: r^{n}=\frac{r^{n}-r^{n+1}}{1-r}, and use telescoping series.

    Have I understood this correctly;

    <br /> <br />
\frac{r^{n}-r^{n+1}}{1-r} = \frac{r^{n}}{1-r} + \frac{-r^{n+1}}{1-r}<br />

     <br />
= \left(\frac{r}{1-r} + \frac{-r^{2}}{1-r}\right) + \left(\frac{r^{2}}{1-r} + \frac{-r^{3}}{1-r}\right) + \left(\frac{r^{3}}{1-r} + \frac{-r^{4}}{1-r}\right) + . . .<br />

     <br />
= \frac{r}{1-r} + \left(\frac{-r^{2}}{1-r}+\frac{r^{2}}{1-r}\right) + \left(\frac{-r^{3}}{1-r} + \frac{r^{3}}{1-r}\right) + . . . <br />

     <br />
= \frac{r}{1-r}<br />


    If that is correct how did you get;

    r^{n}=\frac{r^{n}-r^{n+1}}{1-r}
    Follow Math Help Forum on Facebook and Google+

  4. #4
    MHF Contributor

    Joined
    Aug 2006
    Posts
    18,680
    Thanks
    1618
    Awards
    1
    \begin{gathered}<br />
  S = r + r^2  +  \cdots  + r^n  \hfill \\<br />
  rS = r^2  + r^3  +  \cdots  + r^{n + 1}  \hfill \\<br />
  S - rS = r - r^{n + 1}  \hfill \\<br />
  S = \frac{{r - r^{n + 1} }}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}

    Now \begin{gathered}<br />
  \left| r \right| < 1\quad  \Rightarrow \quad \lim _{n \to \infty } r^{n + 1}  = 0 \hfill \\<br />
  S \to \frac{r}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}
    Follow Math Help Forum on Facebook and Google+

  5. #5
    Junior Member
    Joined
    Jan 2009
    Posts
    44
    Quote Originally Posted by Plato View Post
    \begin{gathered}<br />
S = r + r^2 + \cdots + r^n \hfill \\<br />
rS = r^2 + r^3 + \cdots + r^{n + 1} \hfill \\<br />
S - rS = r - r^{n + 1} \hfill \\<br />
S = \frac{{r - r^{n + 1} }}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}

    Now \begin{gathered}<br />
\left| r \right| < 1\quad \Rightarrow \quad \lim _{n \to \infty } r^{n + 1} = 0 \hfill \\<br />
S \to \frac{r}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}
    awesome, cheers.
    Follow Math Help Forum on Facebook and Google+

  6. #6
    Junior Member
    Joined
    Jan 2009
    Posts
    44
    Quote Originally Posted by Plato View Post
    \begin{gathered}<br />
  S = r + r^2  +  \cdots  + r^n  \hfill \\<br />
  rS = r^2  + r^3  +  \cdots  + r^{n + 1}  \hfill \\<br />
  S - rS = r - r^{n + 1}  \hfill \\<br />
  S = \frac{{r - r^{n + 1} }}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}

    Now \begin{gathered}<br />
  \left| r \right| < 1\quad  \Rightarrow \quad \lim _{n \to \infty } r^{n + 1}  = 0 \hfill \\<br />
  S \to \frac{r}<br />
{{1 - r}} \hfill \\ <br />
\end{gathered}

    What do I google to get more explanation on this? What is this method called?
    Follow Math Help Forum on Facebook and Google+

  7. #7
    Flow Master
    mr fantastic's Avatar
    Joined
    Dec 2007
    From
    Zeitgeist
    Posts
    16,948
    Thanks
    5
    Quote Originally Posted by RhysGM View Post
    What do I google to get more explanation on this? What is this method called?
    sum infinite geometric series: sum infinite geometric series - Google Search=
    Follow Math Help Forum on Facebook and Google+

  8. #8
    MHF Contributor Drexel28's Avatar
    Joined
    Nov 2009
    From
    Berkeley, California
    Posts
    4,563
    Thanks
    21
    I gave you this explanation in the original thread.

    As for Krizalid's answer merely note that r^n=r^n\cdot\frac{r-1}{r-1}=\frac{r^{n+1}-r^n}{1-r}. So, for a finite sum \sum_{k=1}^{n}r^k=\sum_{k=1}^n\frac{r^{k+1}-r^k}{r-1}=\frac{1}{r-1}\sum_{k=1}^{n}\left\{r^{k+1}-r^k\right\} and we notice that the sum is the same as \left(r^2-r\right)+\left(r^3-r^2\right)+\cdots\left(r^{n+1}-r^{n}\right) which simplifies to r^{n+1}-r. Taking the limit n\to\infty finishes the argument.
    Follow Math Help Forum on Facebook and Google+

  9. #9
    Junior Member
    Joined
    Jan 2009
    Posts
    44
    Quote Originally Posted by Drexel28 View Post
    I gave you this explanation in the original thread.
    I know, I didn't understand it then, I needed to do more research before I could understand what you were telling me.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. can anybody prove the g'(x) = g (x)? please
    Posted in the Pre-Calculus Forum
    Replies: 3
    Last Post: February 6th 2011, 03:59 AM
  2. If A^2 = -I then prove...
    Posted in the Advanced Algebra Forum
    Replies: 1
    Last Post: February 3rd 2011, 11:35 PM
  3. Prove(5)
    Posted in the Trigonometry Forum
    Replies: 1
    Last Post: January 22nd 2010, 04:37 AM
  4. Prove the Following
    Posted in the Trigonometry Forum
    Replies: 1
    Last Post: January 17th 2010, 04:11 PM
  5. Replies: 2
    Last Post: August 28th 2009, 02:59 AM

Search Tags


/mathhelpforum @mathhelpforum